2012
DOI: 10.1103/physreva.85.034103
|View full text |Cite
|
Sign up to set email alerts
|

Numerical regularization of electromagnetic quantum fluctuations in inhomogeneous dielectric media

Abstract: Electromagnetic Casimir stresses are of relevance to many technologies based on mesoscopic devices such as microelectromechanical systems embedded in dielectric media, Casimir induced friction in nanomachinery, microfluidics, and molecular electronics. Computation of such stresses based on cavity QED generally requires numerical analysis based on a regularization process. The scheme described below has the potential for wide applicability to systems involving realistic inhomogeneous media. From a knowledge of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…This said, two calculations of Casimir forces in inhomogeneous media have recently been presented [13,14]. In [13] it seems the authors do not yet extract numerical results from their formalism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This said, two calculations of Casimir forces in inhomogeneous media have recently been presented [13,14]. In [13] it seems the authors do not yet extract numerical results from their formalism.…”
Section: Introductionmentioning
confidence: 99%
“…An explicit construction of a regularization procedure that goes beyond that used by Lifshitz has apparently not yet been given, and we suspect that it is not straightforward to do so. Meanwhile, in [14], the concern is with the Casimir force between two mirrors with an inhomogeneous medium sandwiched between them. Here the force is calculated, not via Lifshitz theory but from mode summation, obtaining finite results using techniques similar to ζ -function regularization.…”
Section: Introductionmentioning
confidence: 99%
“…These divergent terms are not canceled by including the contributions to the energy from the other side of the piston, as they were in Eq. (9). This means that in the limit ξ → 0, the force on the piston is discontinuous as a function of α, being finite when α = 0, and infinite as α is moved away from zero.…”
Section: The Inhomogeneous Casimir Pistonmentioning
confidence: 99%
“…The theory has been made quantitative, applying to media described by (ω) and μ(ω) satisfying the Kramers-Kronig relations [2][3][4][5], and Casimir forces have been calculated for a variety of systems and geometries (see, e.g., [6,7]). The purpose of the following discussion is to demonstrate that there seems to be a problem within the theory of the Casimir effect for the case of inhomogeneous media, in spite of recent efforts to solve or circumvent it [8,9]. In a separate paper [10] we have shown that this problem is inherent within the Lifshitz theory of the Casimir effect, where dispersion and dissipation are properly included; the Casimir stress in such cases appears to be infinite, and resists regularization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation